B-spline quasi-interpolant representations and sampling recovery of functions with mixed smoothness - Dinh Dũng (Journal of Complexity, 2016)
Let be a set of n sample points in the d-cube Id≔[0,1]d, and a family of n functions on Id. We define the linear sampling algorithm Ln(Φ,ξ,⋅) for an approximate recovery of a continuous function f on Id from the sampled values f(x1),…,f(xn), by